2008
DOI: 10.32635/2176-9745.rbc.2008v54n2.1747
|View full text |Cite
|
Sign up to set email alerts
|

Linfoma Não-Hodgkin de Alto Grau - Revisão da Literatura

Abstract: Linfomas são transformações neoplásicas de células linfóides normais que residem predominantemente em tecidos linfóides. O linfoma não-Hodgkin (LNH) é a quarta neoplasia mais incidente nos Estados Unidos, excluindo o câncer de pele não-melanoma, e é também a nona causa de morte por câncer no sexo masculino e a sétima no sexo feminino, envolvido em 5% das mortes por câncer. Os linfomas de alto grau são responsáveis por cerca de 50% de todos os casos de LNH e englobam o linfoma não-Hodgkin difuso de grandes célu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…Most of the studied NHL cases were diagnosed as B-cell lymphoma, with a higher incidence of diffuse large B-cell lymphoma (DLBCL) (82; 38.1%) and follicular lymphoma (40; 18.6%). This corresponds to the incidences found in the literature for the different histological subtypes of NHL, which are the high-grade and aggressive subtypes [1,19].…”
Section: Discussionsupporting
confidence: 85%
“…Most of the studied NHL cases were diagnosed as B-cell lymphoma, with a higher incidence of diffuse large B-cell lymphoma (DLBCL) (82; 38.1%) and follicular lymphoma (40; 18.6%). This corresponds to the incidences found in the literature for the different histological subtypes of NHL, which are the high-grade and aggressive subtypes [1,19].…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, it is the ninth leading cause of cancer-related death in males and seventh in females, contributing to 5% of cancer-related deaths. High-grade lymphomas account for approximately 50% of all NHL cases, including anaplastic large-cell lymphoma [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adenopathy predominates in the cervical, supraclavicular, or inguinal chains, but any chain can be affected [ 3 ]. Therefore, biopsy should be recommended whenever a lymph node has the following characteristics: size greater than one centimeter, supraclavicular location, multiple nodal sites, progressive growth, hardened consistency, or adherence to deep planes [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lymphomas are neoplastic transformations of lymphoid cells 8 , most of them with uncertain etiology, but it has been suggested that its development may be related to heredity, environment, occupation, and diet 9,10 . They are classified as either Hodgkin's (HL) or non-Hodgkin's (NHL).…”
Section: Introductionmentioning
confidence: 99%